Effect of the width-to-thickness ratio on the mode I fracture toughness of flexible bonded joints. (September 2019) - Manterola, J.; Cabello, M.; Zurbitu, J.; Renart, J.; Turon, A.; Jumel, J.; Urresti, I.
Highlights: Mode I fracture toughness is influenced by the stress state, governed by t a and B . Elasticity has a strong effect on the fracture behaviour of flexible bonded joints. The lateral contraction due to elasticity is independent to the bondline thickness. Method to predict fracture energy of bonded joints based on stress state analysis. Abstract: The stiffness and strength of a bonded joint mainly depend on the geometry of the assembly and the constitutive behaviour of its constituent parts (adherends, adhesives and interfaces). The adhesive itself may sustain a significant hydrostatic contribution to fluctuation along the bonded area, strongly influencing the local joint stiffness and strength. A considerable amount of work has been undertaken to independently evaluate the effect of the width and thickness of bonded specimens on strength or toughness. However, experimental results are lacking, especially when dealing with thick low modulus/hyperelastic adhesives. In the present work, the influence of the width-to-thickness ratio on the equivalent mode I fracture toughness of a flexible bonded joint is evaluated. Thus, an analytical model capable of predicting the fracture toughness of double cantilever beam (DCB) flexible bonded joints for a given thickness and any width has been developed. The analysis is supported through an experimental testing regime with DCB specimens made by bonding two aluminium adherends with a thick silicon-based adhesive layer, proving that the fracture behaviour of flexible bonded joints is dominated by the elastic behaviour of the adhesive layer.